(untitled) - Levison, Louise (Amsterdam, 2007)
The first, most crucial step in making a film is finding the funds to do it. Let Louise Levison, who wrote the innovative business plan for "The Blair Witch Project," show you how. Whether you're planning a feature, short, documentary, or large format film, this unique guide teaches you how to create a business plan that can be presented to a potential investor. In jargon-free terms, the author leads you through every step. Each chapter concentrates on a different section of the business plan, including the industry, marketing, financing, distribution. There are supplementary exercises and spreadsheets on the CD workbook so you get comfortable crunching the numbers--no math degree required!
Keywords: Motion pictures,Motion picture industry,Ảnh động,Công nghiệp sản xuất ảnh động; Production and direction,Finance,Sản xuất và chỉ đạo,Tài chính